Bacterial Composition of Dairy Base during Fermentation - Mariya V. Gryaznova; Inna Yu. Burakova; Yuliya D. Smirnova; Ekaterina Yu. Nesterova; Natalia S. Rodionova; Evgeniy S. Popov; Mikhail Yu. Syromyatnikov; Vasily N. Popov (Техника и технология пищевых производств)
Probiotic starters are a biological product based on lactic acid bacteria. Their metabolic characteristics determine the properties of the final products. This study evaluated the bacterial composition of a starter culture at various time intervals during the fermentation of a probiotic dairy product. The starter consisted of Streptococcus salivarius ssp. thermophiles, Lactobacillus delbrueckii ssp. bulgaricus, Bifidobacterium bifidum, Bifidobactreium animalis ssp. lactis, Bifidobacterium longum, Lactobacillus acidophilus, and Lacticaseibacillus casei. Pasteurized milk served as the object of fermentation. The starter culture was activated in sterilized skimmed milk. Sampling occurred throughout the entire fermentation process (0, 3, 6, 9, 12, 15, and 18 h). To determine the microbiome of the substrates, the authors used the next-generation high-throughput sequencing that targeted V3 of 16S rRNA gene. The fermentation resulted in a decrease in Bifidobacterium and an increase in Lactobacillus, which peaked (97.5%) after 15 h of fermentation. Each sampling showed that the count of Streptococcus went down. Eventually, Lactobacillus replaced all other genera, including Bifidobacterium, probably, as a result of pH going down during fermentation. The optimal values for the proliferation of Lactobacillus (pH = 4.2–4.4), which were registered after 18 h, turned out to be too low for the productive growth of Bifidobacterium. The research demonstrated the changes in the bacterial composition of the dairy base during fermentation. The high-throughput sequencing proved to be an efficient tool in controlling probiotic fermentation processes.